2021
DOI: 10.1007/s00066-021-01799-w
|View full text |Cite
|
Sign up to set email alerts
|

Improving interinstitutional and intertechnology consistency of pulmonary SBRT by dose prescription to the mean internal target volume dose

Abstract: Purpose Dose, fractionation, normalization and the dose profile inside the target volume vary substantially in pulmonary stereotactic body radiotherapy (SBRT) between different institutions and SBRT technologies. Published planning studies have shown large variations of the mean dose in planning target volume (PTV) and gross tumor volume (GTV) or internal target volume (ITV) when dose prescription is performed to the PTV covering isodose. This planning study investigated whether dose prescription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…The wide variety of prescription patterns and doses in our study indicates that it will be important to obtain interinstitutional and intertechnology consistency in future prospective studies in the oligometastatic setting. A harmonization of planning, dose prescription, technological requirements and reporting is necessary and has already been published for example, lung metastases 41 . Such contouring and planning benchmarking is missing for adrenal metastases and is subject to further research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The wide variety of prescription patterns and doses in our study indicates that it will be important to obtain interinstitutional and intertechnology consistency in future prospective studies in the oligometastatic setting. A harmonization of planning, dose prescription, technological requirements and reporting is necessary and has already been published for example, lung metastases 41 . Such contouring and planning benchmarking is missing for adrenal metastases and is subject to further research.…”
Section: Discussionmentioning
confidence: 99%
“…This underscores the need for even larger datasets to actually detect which doses or approaches lead to long-term LC rates in potential long-term survivors. tion, technological requirements and reporting is necessary and has already been published for example, lung metastases 41. Such contouring and planning benchmarking is missing for adrenal metastases and is subject to further research.…”
mentioning
confidence: 99%
“…1. Based on previous studies, 7,15,17,22,25,29 the prescription dose for all 3 cases was defined as median GTV dose (GTV D50% ) = 3 £ 20 Gy at the 100% isodose line (BED a/ b=10Gy = 180 Gy 10 ). Further target planning objectives were (a) GTV near maximum (ie, GTV D0.1cc ) ≤ 107% = 64.2 Gy (≤110% = 66 Gy), 23,24 (b) GTV coverage at 54 Gy (ie, GTV V90% ) 26 ≥ 98% (≥95%), and (c) PTV coverage at 42 Gy (ie, PTV V70% ) ≥ 98% (≥95%).…”
Section: Treatment Techniques and Treatment Planning Systemsmentioning
confidence: 99%
“…16,[19][20][21] Another way is the strict specification of planning goals and dose prescription, like a recent study on lung SBRT demonstrated. 22 In the lung, tissue heterogeneities are mostly responsible for discrepancies in tumor dose distribution between different patients using common circumferential planning target volume (PTV) prescription methods. 23,24 However, there is a lack of benchmark planning studies for larger tumors in more homogeneous tissue closer to critical organs at risk (OAR), like liver metastases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation